(untitled) (Eurasian Journal of Ecology, 2018)
Bacterial cellulose (BC) is a promising biopolymer with unique properties that make it possible to widely use it in biomedicine, tissue engineering, electrical engineering, food and textile industries. The aim of a work was to determine the productivity of bacterial cellulose biosynthesis by propagation of a producer strain on media on the basis of agricultural and food wastes. In present work, the effect of various culture media on strain productivity and structural properties of BC was studied. Three types of fermentation media on the basis of agro- and food-processing wastes were used. The productivity of the strain was evaluated according to biomass yield and BC weight by gravimetric method. The morphology of BC films was studied by SEM method, and mechanical characteristics – by «Instron» tensile machine. The maximum yield of BC – 8.21+0.02 g/l was achieved by cultivating of a producer on medium containing wastes of sugar production – molasses. The resulting materials formed on classical HS medium and industrial waste media had an interconnected porous matrix structure with a large surface area. Micro- (15-35 nm) and macrofibrils (50-150 nm) in BC films formed on a medium with molasses joined into ribbon-like fibers, providing high mechanical strength (tensile strength: 37.12+0.2, elongation : 3.28+0.2%). Key words: bacterial cellulose, fermentation medium, Gluconacetobacter xylinus, industrial wastes